Enfermedades del frijol causadas por bacterias - Pastor Corrales, Marcial A. (United Nations Development Programme, 1985)
The etiology, symptomatology, cultural and chemical control measures, and general aspects of control through var. resistance to bean diseases are described for the bacterial pathogens Pseudomonas syringae pv. phaseolicola and Xanthomonas campestris pv. phaseoli. Some var. resistant to these pathogens are listed. (CIAT)